Metaphors of Desire in Women's Writing in English - Gjurgjan, Ljiljana Ina (1995)
Starting with the contention that there is a complex relation between metaphors and the reality to which they point, the paper draws on the body of women's texts in order to classify and compare the most characteristic metaphors of desire. those are then grouped into two main types. The first type appears in opposition to images of claustrophobia, suffocation, headache etc. which reflect the reality of a constricting kind of women's situation. Reacting against these are such metaphors of desire that appear to be an expression of cultural stereotypes and therefore a form of oppression. The second group of metaphors expresses rebellion and desire for change. Metaphors of subverted order, of carnival and transdressing, as well as of awakening and surfacing belong to this group. They point towards the need for social change and towards a non-oppressive system of values.